Hydrocarbon - Kutcherov, Vladimir; Kolesnikov, Anton (IntechOpen, 2013)
Hydrocarbons provide our core energy resource. Information on their origin, properties and phase behavior is interesting from the point of view of physical chemistry. At the same time this information is of great value to the oil and gas industry. The book "Hydrocarbon" is comprised of 9 chapters, covering different topics: from origin of hydrocarbons to the method for hydrocarbon exploration. Distribution of polycyclic aromatic hydrocarbons in soil and their influence to environment are also discussed. This book should serve as a support to researchers and students as well as experts, both in academia and industry.